ELIAS DAVID CURIEL: COLGADO AL ÁRBOL DE LA SOLEDAD (De la Crítica, 2024)
The essay presented below aims to investigate classical sources and contemporary works that feed the imagination of the falconian poet Elías David Curiel, considered one of the precursors of modernism in Venezuela, through opinions expressed by researchers who have carried out exhaustive studies that lead to the points of origin of the topic addressed in his outstanding poetic work.